Single Incision Laparoscopic Total Gastrectomy and D2 Lymph Node Dissection for Gastric Cancer Using a Four-Access Single Port: The First Experience - Metin Ertem; Emel Ozveri; Hakan Gok; Volkan Ozben (Case Reports in Surgery)
Single incision laparoscopic surgery (SILS) and natural orifice transluminal endoscopic surgery (NOTES) have been developed to reduce the invasiveness of laparoscopic surgery. SILS has been frequently applied in various clinical settings, such as cholecystectomy, colectomy, and sleeve gastrectomy. So far, there have been four reports on single incision laparoscopic distal gastrectomy and one report on single incision laparoscopic total gastrectomy with D1 lymph node dissection for gastric cancer. In this report, we present our single incision laparoscopic total gastrectomy with D2 lymph node dissection technique using a four-hole single port (OctoPort) in a patient with gastric cancer.